Retraction of 'Chemical investigation of Cyperus articulatus' (J App Pharm Sci, 2014, 4(11): 095-097) (Journal of Applied Pharmaceutical Science, 2014)
Article entitled Chemical investigation of Cyperus articulatus' by Shariful Haque, Mohi Uddin, Mohd Omar Faruk Sikder, Mohammad Riaz (J App Pharm Sci, 2014, 4(11): 095-097) has been retracted, at the request of the Authors. The authors have decided to retract this article because of conflicts amongst the authors.